2009
DOI: 10.3174/ajnr.a1326
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Oxygen Level–Dependent Functional MR Imaging Signal Can Be Used to Identify Brain Tumors and Distinguish Them from Normal Tissue

Abstract: BACKGROUND AND PURPOSE:In neuro-oncology, a major problem is clear identification of tumor from the surrounding normal tissue. We hypothesized that we could use the blood oxygen level-dependent functional MR imaging (BOLD fMRI) signals from tumors and normal brain to identify the tumors and distinguish them from the surrounding brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
5
23
0
1
Order By: Relevance
“…Our findings seem to concur with the hypothesis that abnormal tumor neovasculature, a pathologic hallmark of GBMs, contributes to neurovascular uncoupling, which might lead to a decrease in BOLD functional MR imaging activation at the ipsilateral hemisphere (14,18,19,27). Yet, we draw attention to the fact that the significant interhemispheric difference in BOLD functional MR imaging activation observed in GBMs, but not within metastases and meningiomas, does not prove per se that there is a difference in this respect between the three tumor types.…”
Section: Neuroradiology: Influence Of Tumor Type and Bold Functional supporting
confidence: 90%
See 1 more Smart Citation
“…Our findings seem to concur with the hypothesis that abnormal tumor neovasculature, a pathologic hallmark of GBMs, contributes to neurovascular uncoupling, which might lead to a decrease in BOLD functional MR imaging activation at the ipsilateral hemisphere (14,18,19,27). Yet, we draw attention to the fact that the significant interhemispheric difference in BOLD functional MR imaging activation observed in GBMs, but not within metastases and meningiomas, does not prove per se that there is a difference in this respect between the three tumor types.…”
Section: Neuroradiology: Influence Of Tumor Type and Bold Functional supporting
confidence: 90%
“…Finally, the other MR imaging features examined, volume of enhancement and tumor location, did not seem to play a role. The explanation may be that BOLD response is inherently a vascular phenomenon, which is marginally affected by tumor size (18,27). However, this should be interpreted with caution, as the exact determination of tumor volumes at routine MR imaging is difficult in gliomas, in which borders are often ill defined (30).…”
Section: Neuroradiology: Influence Of Tumor Type and Bold Functional mentioning
confidence: 99%
“…BOLD imaging was also used in patients with brain tumors during a given task and during rest (resting-state fMRI), to study brain activation and to distinguish tumoral from non-tumoral tissue [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown malignancies in the brain (meningiomas, gliomas or metastasis) can be distinguished from normal brain tissues using BOLD-MRI and in older patients with grade IV gliomas, BOLD signal intensity is equivalent to that measured in younger patients with grade IV gliomas, whereas in patients with grade II and III gliomas, BOLD-MRI signal change correlated only with increasing age [166,167].…”
Section: Imaging Hypoxia In Gliomasmentioning
confidence: 89%